A clean and efficient method for purifying crude selenium based on a selective leaching - directed decomposition purification process. (1st October 2022) - Xu, Na; He, Xiaocai; Xu, Qingxin; Diao, Weizhi; Yan, Sen; He, Qiugu; Ren, Tin
Abstract: The rare element selenium is a key material in supporting the development of high-tech and new products. This research has led to the development of a method of purifying crude selenium based on a selective leaching-directed decomposition purification process. The influence of factors such as the concentration of the leaching solution, leaching temperature, solid-liquid ratio, and leaching time on the leaching rate of Se were investigated in detail. The experimental results show that the optimal conditions for selective leaching of selenium were as follows: the concentration of leaching solution (solute: Na2 SO3 ) was 260 g l −1, the stirring speed was 300 rpm, the ratio of liquid to solid was 0.10 g ml −1, the reaction temperature was 90 °C, the reaction time was 180 min, and the leaching rate of selenium on one run was >95%. The products of selenium after two runs meet the requirements of Se99.9 in YS/223–2007, the Chinese nonferrous metal industry standard. The direct yield of Se is greater than 90%, and precious metals such as gold, silver and platinum are enriched in the residue. No waste is produced during the whole purification process, and all products can be recycled. This study provides an efficient and environmentally friendly method for the purification of crude selenium, which has important industrial applications.